Dynamic pulmonary CT perfusion using first-pass analysis technique with only two volume scans: Validation in a swine model - Zhao, Yixiao (PLoS One, 2020)
PURPOSE: To evaluate the accuracy of a low-dose first-pass analysis (FPA) CT pulmonary perfusion technique in comparison to fluorescent microsphere measurement as the reference standard. METHOD: The first-pass analysis CT perfusion technique was validated in six swine (41.7 ± 10.2 kg) for a total of 39 successful perfusion measurements. Different perfusion conditions were generated in each animal using serial balloon occlusions in the pulmonary artery. For each occlusion, over 20 contrast-enhanced CT images were acquired within one breath (320 x 0.5mm collimation, 100kVp, 200mA or 400mA, 350ms gantry rotation time). All volume scans were used for maximum slope model (MSM) perfusion measurement, but only two volume scans were used for the FPA measurement. Both MSM and FPA perfusion measurements were then compared to the reference fluorescent microsphere measurements. RESULTS: The mean lung perfusion of MSM, FPA, and microsphere measurements were 6.21 ± 3.08 (p = 0.008), 6.59 ± 3.41 (p = 0.44) and 6.68 ± 3.89 ml/min/g, respectively. The MSM (P(MSM)) and FPA (P(FPA)) perfusion measurements were related to the corresponding reference microsphere measurement (P(MIC)) by P(MSM) = 0.51P(MIC) + 2.78 (r = 0.64) and P(FPA) = 0.79P(MIC) + 1.32 (r = 0.90). The root-mean-square-error for the MSM and FPA techniques were 3.09 and 1.72 ml/min/g, respectively. The root-mean-square-deviation for the MSM and FPA techniques were 2.38 and 1.50 ml/min/g, respectively. The CT dose index for MSM and FPA techniques were 138.7 and 8.4mGy, respectively. CONCLUSIONS: The first-pass analysis technique can accurately measure regional pulmonary perfusion and has the potential to reduce the radiation dose associated with dynamic CT perfusion for assessment of pulmonary disease.